2019
DOI: 10.3390/ijms20153761
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Response of Growth Plate to Biodegradable Mg-Ca-Zn Alloys Depending on the Surface Modification

Abstract: Because Mg-Ca-Zn alloys are biodegradable and obviate secondary implant removal, they are especially beneficial for pediatric patients. We examined the degradation performance of Mg-Ca-Zn alloys depending on the surface modification and investigated the in vivo effects on the growth plate in a skeletally immature rabbit model. Either plasma electrolyte oxidation (PEO)-coated (n = 18) or non-coated (n = 18) Mg-Ca-Zn alloy was inserted at the distal femoral physis. We measured the degradation performance and fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The DRs calculated for both implantation sites accounted 0.23–0.75 mm/year. This lies within the range of DRs of different Mg alloys found in the literature [ 30 , 31 ]. Chaya et al .…”
Section: Discussionsupporting
confidence: 82%
“…The DRs calculated for both implantation sites accounted 0.23–0.75 mm/year. This lies within the range of DRs of different Mg alloys found in the literature [ 30 , 31 ]. Chaya et al .…”
Section: Discussionsupporting
confidence: 82%
“…29,76 Afterward, continuous surface modification of K-MET was further performed to achieve optimal degradation rates without damaging the growth plate. 77 3.3.3. In Japan.…”
Section: In South Koreamentioning
confidence: 99%
“…The concentrations of Mg 2 +, Ca 2 +, and Zn 2 + in local tissues were maintained within normal ranges during the degradation of Mg-Ca-Zn alloys. 162 In animal experiments, PEO-coated Mg-Ca-Zn alloy scaffold were implanted into the rabbit growth plate defects. The results showed that the implants did not cause significant immune response after implantation.…”
Section: Syntheticmentioning
confidence: 99%